2017
DOI: 10.1111/nan.12408
|View full text |Cite|
|
Sign up to set email alerts
|

Age‐associated changes in the blood‐brain barrier: comparative studies in human and mouse

Abstract: AimsWhile vascular pathology is a common feature of a range of neurodegenerative diseases, we hypothesized that vascular changes occur in association with normal ageing. Therefore, we aimed to characterize age‐associated changes in the blood–brain barrier (BBB) in human and mouse cohorts.MethodsImmunohistochemistry and Evans blue assays were used to characterize BBB dysfunction (tight junction protein expression and serum plasma protein accumulation), vascular pathology (pericyte loss and vascular density) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 48 publications
(55 reference statements)
6
68
3
1
Order By: Relevance
“…This model exhibits both Aβ and NFTs allowing assessment of astrocyte response to both pathological features, and therefore may recapitulate aspects of AD more effectively than the J20 mouse model which only overexpresses levels of Aβ. A recent study by Goodall et al [67] reported an overall ageassociated increase in astrocyte activation in C57 mice, but in the current study this pattern was not observed and the lack of genotype-or age-associated proliferation may be partially attributable to astrocyte atrophy. Moreover, astrocyte atrophy can lead to synapse loss and reduced neuronal metabolic support, which can ultimately result in early cognitive deficits [66].…”
Section: Discussioncontrasting
confidence: 88%
“…This model exhibits both Aβ and NFTs allowing assessment of astrocyte response to both pathological features, and therefore may recapitulate aspects of AD more effectively than the J20 mouse model which only overexpresses levels of Aβ. A recent study by Goodall et al [67] reported an overall ageassociated increase in astrocyte activation in C57 mice, but in the current study this pattern was not observed and the lack of genotype-or age-associated proliferation may be partially attributable to astrocyte atrophy. Moreover, astrocyte atrophy can lead to synapse loss and reduced neuronal metabolic support, which can ultimately result in early cognitive deficits [66].…”
Section: Discussioncontrasting
confidence: 88%
“…A recent study demonstrated an increase in gliosis and GFAP expression associated with ageing in mice, but did not observe a change in the number or morphology of astrocytes. Astrocytes are the major source of lipoprotein constituents and lipoprotein assembly in the brain .…”
Section: Discussionmentioning
confidence: 87%
“…18 Some studies have found evidence that pericyte loss with ageing is associated with BBB breakdown in mice, but loss of pericyte coverage in the human brain capillaries was shown to have no correlation with age. 19 We can speculate that the loss of pericytes may stimulate BM synthesis by endothelial cells leading to an increase in the BM thickness with age.…”
Section: Discussionmentioning
confidence: 95%
“…; Goodall et al . ). In contrast, loss of astrocytes and retraction of the end feet which express the transmembrane protein aquaporin 4 (AQP4) that forms channels selective for water mobility (Nagelhus and Ottersen ) were severely affected in the DWML (Chen et al .…”
Section: Gliovascular Interactions and The Bbb In Wmmentioning
confidence: 97%
“…Abnormalities in these proteins have been observed in a number of disorders associated with BBB dysfunction (Sandoval and Witt 2008;Weiss et al 2009). Quantification of these proteins to assess disruption of tight junctions and use as surrogate markers of BBB permeability indicated that these were not significantly affected in MRI defined DWML, although there was widespread albumin extravasation (Simpson et al 2010;Goodall et al 2017). In contrast, loss of astrocytes and retraction of the end feet which express the transmembrane protein aquaporin 4 (AQP4) that forms channels selective for water mobility (Nagelhus and Ottersen 2013) were severely affected in the DWML (Chen et al 2016).…”
Section: Gliovascular Interactions and The Bbb In Wmmentioning
confidence: 99%